Developmental Needs of Small Children. Threats and Potential Consequences of Transferring Children to Nursery - Dudziak, Urszula (Studia Warmińskie, 2024)
A child’s proper development requires love expressed through close parental care and contact that allows for the establishment of bonds. Many parents place their children in a day nursery due to the economic needs of society, their career development, the desire to increase the family’s financial standard, impatience with their own children, ignorance of the rules of care and upbringing, and the belief that professional educators can perform educational tasks better. Politicians compete to highlight the growing number of such facilities and funds allocated for their maintenance. However, it is questionable whether separating parents who go to work and children who are placed in a day nursery has a positive effect on the children’s development process. Is this practice an expression of parental care, or does it cause conscious or unconscious harm to the younger generation? What do people who care about the child’s best interest focus on, and how can they create the best conditions for their development? What steps can be taken to make the initial stages of a child’s life as appropriate as possible, considering it is the foundation of shaping proper attitudes in the future? This article is based on a review of both theoretical and empirical publications, which supports the presented conclusions and postulates.